Differential processing of natural scenes in posterior cortical atrophy and in Alzheimer’s disease, as measured with a saccade choice task - Boucart, Muriel; Calais, Gauthier; Lenoble, Quentin; Moroni, Christine; Pasquier, Florence (Frontiers in Integrative Neuroscience, 2014)
Atrophy of the medial temporal lobe structures that support scene perception and the binding of an object to its context (i.e., the hippocampus and the parahippocampal cortex) appears early in the course of Alzheimer’s disease (AD). However, few studies have investigated scene perception in people with AD. Here, we assessed the ability to find a target object within a natural scene in people with AD and in people with posterior cortical atrophy (PCA, a variant of AD). Pairs of color photographs were displayed on the left and right of a fixation cross for 1 s. In separate blocks of trials, participants were asked to categorize the target (an animal) by either moving their eyes toward the photograph containing the target (the saccadic choice task) or pressing a key corresponding to the target’s location (the manual choice task). Isolated objects and objects within scenes were studied in both tasks. Participants with PCA were more impaired in detection of a target within a scene than participants with AD. The latter’s performance pattern was more similar to that of age-matched controls in terms of accuracy, saccade latencies and the benefit gained from contextual information. Participants with PCA benefited less from contextual information in both the saccade and the manual choice tasks—suggesting that people with posterior brain lesions have impairments in figure/ground segregation and are more sensitive to object crowding.